Anti-allodynic and antihyperalgesic properties of zerumbone and their mechanisms of action in mice model of neuropathic pain - Gopalsamy, Banulata (2017)
Neuropathic pain is a chronic pain condition that affects almost 6-10% of the world population severely affecting their quality of life. To date, conventional drugs could not provide complete pain relief and therefore alternative treatments are rapidly sought after. Zerumbone, a compound isolated from Zingiber zerumbet, was reported to exhibit anti-inflammatory and antinociceptive properties and therefore will able to attenuate the symptoms of neuropathic pain. This study was carried out to evaluate the properties of zerumbone in a chronic constriction injury (CCI)-induced mice model of neuropathic pain. The first study was conducted to characterise the various neuropathic pain models developed with different number of ligations. The outcome showed that single ligation was sufficient to well-surrogate this model as the models with different number of ligations showed similar levels of allodynia, hyperalgesia, nerve degeneration and expressions of pain marker, c-fos. Following that, this study elucidated the anti-allodynic and antihyperalgesic properties of zerumbone at doses 10 and 50 mg/kg; i.p. However, at the optimal dose of 10 mg/kg, zerumbone did not show any distinct reduction in c-fosexpression. However, zerumbone does not maintain the nerve integrity or delay the nerve degeneration process following nerve injury. Nevertheless, zerumbone successfully suppressed Interleukin (IL)-1β, IL-6, Tumor Necrosis Factor (TNF)-α but not IL-10 in blood plasma and spinal cord at doses 10 and 50mg/kg; i.p. The following study demonstrated that the action of zerumbone lasts for two hours upon both single and long-term repeated treatments. Furthermore, zerumbone was able to reduce stimulus-induced-c-fosexpressions at the spinal cord, cingulate cortex and parafascicular nuclei regions of the brain indicating antinociceptive properties of zerumbone at specific sites. This study further supported the results by demonstrating the involvements of the opioidergic system, specifically the μ-, ҡ- and δ-opioid subtypes in the attenuation of allodynia and hyperalgesia by zerumbone. Moreover, the involvement of potassium (K+) channels including the voltage gated K+ channels (Kv), ATP-sensitive K+ channels (KATP), small and large conductance calcium activated K+ channels in zerumbone-induced analgesia has also been elucidated. In conclusion, zerumbone exhibits anti-allodynic, antihyperalgesic and anti-inflammatory properties providing evidencethat zerumbone might be a potential lead compound for the treatment of neuropathic pain.